Reforms in German, French and British health systems - Ferreira, Mariana Ribeiro Jansen (2018)
Objectives: To map the reforms experienced in German, French and British health systems over the period 1980, 1990 and 2000, as well as to present the recent modifications by means of the economic crisis of 2008/2009. Methods: This is an original article based on the approach of the political economy method, through the historical description of change processes in the commodification of the health systems, with qualitative characteristics. For examination of the series of changes seen in the health systems, a comparative analysis is used, addressing these aspects: cost-containment mechanisms; instruments of commodification; decentralization of management and allocation of resources; regulation; financing; and coverage. Results: Over the analyzed decades, the three health systems experienced reforms that involved: new forms of financing; expansion of co-payments, private insurance, public-private partnerships, outsourcing of auxiliary services, private patient care in the public network; incorporation of the private sector in the provision of services; private management of public institutions; increased competition between public service providers; payment by results in hospitals. Conclusion: The reforms generated more commoditized and cost-oriented systems, but in which the social demand forced the extension of coverage, with increasing use of fiscal resources for their financing.